ANALISIS LITERASI DIGITAL DI SDN 195 PALEMBANG - Ahyina Hubbal Faizin; Lasmiati; Landi Lebriansyah; Nabila; Abellia (PT. Hasba Edukasi Mandiri, 2025)
This research focuses on evaluating the integration of digital literacy practices at SD Negeri 195 Palembang utilizing observation techniques, in-depth interviews, and student questionnaire distribution. Digital competency represents an essential 21st-century skill set that should be cultivated from primary education levels; yet its application across educational settings continues to encounter multiple obstacles. The study adopted a descriptive design through a combined qualitative-quantitative methodology. Information gathering was conducted via school infrastructure observation, dialogues with school administrators and teaching staff, and survey distribution to 30 pupils from grades III, V, and VI. Research outcomes reveal that SDN 195 Palembang has initiated digital literacy implementation by utilizing basic digital tools, the WhatsApp platform for communication purposes, and introductory coding activities for senior-grade learners. Primary challenges include inadequate facilities such as only two available projectors, non-existent computer laboratories, and inconsistent internet access. Survey data demonstrates that pupils' digital literacy competence reaches the high classification with a mean score of 79%. Conversely, dimensions concerning digital security and online ethics remain at moderate levels, registering 51%. In summary, digital literacy practices at SDN 195 Palembang have advanced reasonably well, though enhancements are necessary through infrastructure expansion, educator capacity building, and reinforcement of digital safety and ethical education from early stages.